Determination of Minimum Miscibility Pressure of Crude Oil–CO2 System by Oil Swelling/Extraction Test. Issue 5 (18th March 2014) - Abedini, Ali; Mosavat, Nader; Torabi, Farshid
Abstract: The minimum miscibility pressure (MMP) of crude oil–CO2 systems was determined through analyzing the experimental data of swelling/extraction tests. First, the oil swelling factor (SF) as a result of CO2 dissolution in a crude oil sample was determined at four different temperatures in the range of T =21–40 °C. In addition, three sets of swelling/extraction data of previous studies were collected and included so that more conclusive and satisfactory results can be obtained. The results demonstrated that the oil swelling factor increases with the equilibrium pressure ( P eq ), reaches the maximum value at light hydrocarbon extraction pressure ( P ext ), and then reduces with further increase in equilibrium pressure. It was found that the reduction behavior of oil swelling factor occurs in two distinct regions. In the upper extraction phase (UEP), the oil swelling factor decreased sharply at pressures just over extraction pressure and then declined gradually in what is called the lower extraction phase (LEP). Finally, the MMP of the crude oil–CO2 system at a specific temperature was estimated by finding the intersection of the linear regression correlation corresponding to each of the aforementioned regions (i.e., UEP and LEP). The crude oil–CO2 MMP was also determined by employing the vanishing interfacial tension (VIT) technique and a series of CO2 injection tests. Comparing the MMP values of the crude oil–CO2 systems determined by three methods revealed that the MMP values estimated by swelling/extraction data are in approximate agreement with those determined by the two other methods. Abstract : Pressure to mix: The minimum miscibility pressure (MMP) of crude oil–CO2 systems is determined by measuring the oil swelling factor and analyzing the experimental data of swelling/extraction tests. The oil swelling factor increases with the equilibrium pressure ( P eq ), reaches the maximum value at light hydrocarbon extraction pressure ( P ext ), and then reduces with further increase in equilibrium pressure. MMP values obtained by the different methods are in agreement.